DEVS-based combat modeling for engagement-level simulation. (July 2014) - Seo, Kyung-Min; Choi, Changbeom; Kim, Tag Gon; Kim, Jung Hoon
This paper presents a modeling method to demonstrate engagement-level military simulation which includes few combat objects, or entities. To this end, the paper, on the basis of the discrete event system specification (DEVS) formalism, centers on two ideas: (1) a combat entity's model structure at the composition level; and (2) behavioral delineation of the entity's elementary component. In detail, we classify the combat entity model into platform and weapon models and create six groups of the model categorized by two dimensions: three activities and two abstractions. And the elementary component in the group interprets an engagement scenario as a flow of executable tasks, which are expressed by DEVS semantics. The stated structures and semantics provide intuitive appeal, reducing the effort required to read and understand the model's behavior. From the combat experiments, we can gain interesting experimental results regarding engagement situations employing underwater weapons and their tactical operations. Finally, we expect that this work will serve an immediate application suited to various engagement situations.